FACTORS ASSOCIATED WITH THE OCCURRENCE OF INTESTINAL PARASITES IN CHILDREN LIVING IN THE FEDERAL DISTRICT OF BRAZIL - Santos, Alessandro Abreu dos; Gurgel-Gonçalves, Rodrigo; Machado, Eleuza Rodrigues (Revista de Patologia Tropical / Journal of Tropical Pathology, 2014)
This study aimed to describe factors associated with the occurrence of intestinal parasites in children living in the Federal District of Brazil (FD). Between 2012 and 2013 fecal samples from 193 children of Riacho Fundo II (RF, n=73) and Ceilândia (CE, n=120) were examined using Rugai and Lutz’s methods. Socioeconomic and health variables were obtained through interviews with the children’s parents. The association between these variables and the occurrence of parasites was analyzed by chi-squared or Fisher’s exact tests. The occurrence of parasites in RF (79%) was higher than in CE (54%). The most frequent parasites were Giardia intestinalis (RF=15%, CE=9%), Hymenolepis nana (RF=44%, CE=0%) and Ascaris lumbricoides (RF=30%, CE=2%). In CE, a higher frequency of parasites was found in children living in crowded houses and also in houses with domestic animals present. In RF, a higher frequency of parasites was found in children whose families did not wash fruit and vegetables hygienically. A relevant occurrence of intestinal parasites in children was found in the FD, where there is a treated water supply and sewage system. We concluded that poor hygiene habits are the key factors in the transmission of intestinal parasites in FD.